Comparison of the apple vinegar with other chelating solutions on smear layer and calcium ions removal from the root canal - A L Kirchhoff; R Viapiana; CES Miranda; M D Sousa Neto; A M Cruz Filho (Wolters Kluwer Medknow Publications, 2014)
Background: The action of endodontic instruments during biomechanical preparation results in smear layer formation. Removing the smear layer enhances disinfection into dentinal tubules in addition to allowing tridimensional sealing of the root canal system. Aim: This study was designed to evaluate the smear layer removal and quantify the calcium ion release resulting from final irrigation with different chelating solutions. Materials and Methods: Fifty human canines were instrumented and the final irrigation was performed with apple vinegar, 5% malic acid, 5% acetic acid, 17% ethylenediamine tetra-acetic acid (EDTA), and distilled water (control), which were collected and analyzed by atomic absorption spectrometry to quantify the concentration of calcium ions released. Smear layer removal was assessed in the cervical, middle, and apical thirds by SEM. Results: There was statistically significant difference (P < 0.001) between 17% EDTA and the other solutions with regard to smear layer removal. Apple vinegar, 5% malic acid, and 5% acetic acid promoted similar root canal cleaning. There was no statistical difference among the root canal thirds. The highest concentrations of calcium ions were obtained with 17% EDTA (P<0.001) followed by malic acid, apple vinegar, and acetic acid. Apple vinegar and acetic acid removed the smallest quantity of calcium ions. Conclusion: It was concluded that 17% EDTA enabled greater smear layer removal and promoted release of the highest concentrations of calcium ions than the other solutions tested.